Human Capital Evaluation with Social Network Analysis Support - Fryczyńska, Marzena (Edukacja Ekonomistów i Menedżerów, 2013)
The purpose of this article is to show the social network analysis as the perspective of human capital evaluation. It presents interrelation between the social and human capital, the brief introduction to social network theory and its analyzing method. However, social network analysis (SNA) is the method to evaluate social capital, the author pointed out the possible SNA metrics essential in the human capital evaluation. The article shows the SNA and human capital in the individual perspective – ego. It provides the idea of the human capital evaluation in broader and more precise way.